ANALISIS BAURAN PEMASARAN OFFLINE DAN ONLINE PADA AGROINDUSTRI KERIPIK BINTANG BUAH DI KOTA BANDAR LAMPUNG - Denti Fitri Yanti; Dyah Aring Hepiana Lestari; Rabiatul Adawiyah (Jurnal AGRISEP, 2025)
The Fruit Processing Industry is a food manufacturer that uses fresh fruit as raw materials to produce products such as jackfruit chips and banana chips. The rapid development of technology has pioneered the online marketing of products. The objective of this study is to compare the purchasing decisions of offline and online consumers in the Fruit Processing Industry in Bandar Lampung City in 2023. The respondents in this study consist of 30 offline consumers and 30 online consumers. Data collection was conducted from February to March 2023. The analysis method used is the 4P marketing mix analysis (product, price, place, and promotion) followed by the Mann-Whitney test. The results indicate that the average variable for offline and online consumers falls into the good category with a percentage of 78.08 percent and 79.85 percent respectively. The Mann-Whitney test results show no significant differences in consumer decision-making between online and offline channels concerning price and promotion. In contrast, significant differences exist for product and place, underscoring their influence on purchasing behavior. Based on the research findings, to balance purchasing decisions between offline and online, it is recommended that the small Fruit Processing Industry in Bandar Lampung City add special discounts or prices for purchases on certain days and adjust promotions to current trends to increase sales.